Process optimisation, characterisation and evaluation of resveratrol-phospholipid complexes using Box-Behnken statistical design - Agarwal, Apoorva; Kharb, Vandana; Saharan, Vikas Anand (International Current Pharmaceutical Journal, 2014)
With the advent of 21st century, researchers worldwide have extensively reviewed herbs and botanicals for their marked clinical efficacy. It has been estimated that most of the newly discovered compounds offer poor bioavailability due to their low aqueous solubility. Phospholipid complexation of the drug often helps to improve its water solubility and enhance the bioavailability. This study includes optimization of resveratrol-phospholipid complexes using a 3-factor, 3-level box-behnken design (15 batches). Three independent variables i.e. phospholipid-resveratrol ratio, refluxing temperature and reflux time were optimized for two dependent variables, i.e. yield and entrapment efficiency (EE). Complexes were prepared by refluxing stoichiometric ratio of Phospholipon 90G and resveratrol in dichloromethane and retrieved by precipitation with n-hexane. Complexation was confirmed by Fourier Transform Infra-Red (FTIR) spectroscopy. The data was suitably used to explore quadratic response surfaces and construct second order polynomial models with Design Expert®. Formulation with highest desirability (D=0.994) was selected as optimum and prepared using 1.5:1 Phospholipon 90G-resveratrol ratio (X1) at 59.4°C temperature (X2) and 4 h time (X3) to give maximum yield and entrapment efficiency. Analysis of variance (ANOVA) was also found to be significant for both the responses. Complexes were optimised for good yield and EE. The partition coefficient was lowered to 2.25 hypothesizing good passive absorption. DOI: http://dx.doi.org/10.3329/icpj.v3i7.19079 International Current Pharmaceutical Journal, June 2014, 3(7): 301-308